Leukocyte adhesion deficiency-1 with oral manifestations - A rare case report - Sethumanjusha Saranu; Yalamanchili Samata; Nunsavathu Purnachandra Rao Naik; Garikipati Anoop (Wolters Kluwer Medknow Publications, 2022)
Leukocyte adhesion deficiency 1 (LAD) is a rare, inherited disorder portrayed by the inability of leukocytes to emigrate from the bloodstream toward sites of inflammation. LAD should be considered a rare but possible disorder in patients with persistent periodontal problems. This paper presents a case of leukocyte adhesion deficiency in an 18-year-old girl and a brief literature review.